Advances in Molecular Understanding of α-Helical Membrane-Active Peptides - Kabelka, Ivo; Vácha, Robert (Accounts of chemical research, 2021)
Biological membranes separate the interior of cells or cellular compartments from their outer environments. This barrier function of membranes can be disrupted by membrane-active peptides, some of which can spontaneously penetrate through the membranes or open leaky transmembrane pores. However, the origin of their activity/toxicity is not sufficiently understood for the development of more potent peptides. To this day, there are no design rules that would be generally valid, and the role of individual amino acids tends to be sequence-specific.In this Account, we describe recent progress in understanding the design principles that govern the activity of membrane-active peptides. We focus on α-helical amphiphilic peptides and their ability to (1) translocate across phospholipid bilayers, (2) form transmembrane pores, or (3) act synergistically, i.e., to produce a significantly more potent effect in a mixture than the individual components.We refined the description of peptide translocation using computer simulations and demonstrated the effect of selected residues. Our simulations showed the necessity to explicitly include charged residues in the translocation description to correctly sample the membrane perturbations they can cause. Using this description, we calculated the translocation of helical peptides with and without the kink induced by the proline/glycine residue. The presence of the kink had no effect on the translocation barrier, but it decreased the peptide affinity to the membrane and reduced the peptide stability inside the membrane. Interestingly, the effects were mainly caused by the peptide's increased polarity, not the higher flexibility of the kink.Flexibility plays a crucial role in pore formation and affects distinct pore structures in different ways. The presence of a kink destabilizes barrel-stave pores, because the kink prevents the tight packing of peptides in the bundle, which is characteristic of the barrel-stave structure. In contrast, the kink facilitates the formation of toroidal pores, where the peptides are only loosely arranged and do not need to closely assemble. The exact position of the kink in the sequence further determines the preferred arrangement of peptides in the pore, i.e., an hourglass or U-shaped structure. In addition, we demonstrated that two self-associated (via termini) helical peptides could mimic the behavior of peptides with a helix-kink-helix motif.Finally, we review the recent findings on the peptide synergism of the archetypal mixture of Magainin 2 and PGLa peptides. We focused on a bacterial plasma membrane mimic that contains negatively charged lipids and lipids with negative intrinsic curvature. We showed that the synergistic action of peptides was highly dependent on the lipid composition. When the lipid composition and peptide/lipid ratios were changed, the systems exhibited more complex behavior than just the previously reported pore formation. We observed membrane adhesion, fusion, and even the formation of the sponge phase in this regime. Furthermore, enhanced adhesion/partitioning to the membrane was reported to be caused by lipid-induced peptide aggregation.In conclusion, the provided molecular insight into the complex behavior of membrane-active peptides provides clues for the design and modification of antimicrobial peptides or toxins.
Keywords: buněčná membrána; Lipids; Peptides; peptidy; Protein Conformation, alpha-Helical; konformace proteinů, alfa-helix; lipidy; Cell Membrane